Frictional Resistance of Two Types of Esthetic Self-Ligating Brackets - HA Kamil; ShSh Taha (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Friction between the archwire and bracket is the main problem during tooth movement. Self-ligating bracket systems have become common in recent years. The aim of this study was to investigate and compare the effect of active and passive esthetic self-ligating brackets on static frictional force with different orthodontic archwires under wet conditions. Methods: This in vitro study included 180 ceramic self-ligating brackets, 90 passive brackets (Damon Clear), and 90 active brackets (Empower Clear), which were tested for frictional resistance using three different types of 0.018-inch archwires, namely copper NiTi archwires and two esthetic archwires (Epoxy- and rhodium-coated NiTi archwires). According to the types of brackets and archwires, six groups of ten were defined. An experimental model with three non-leveled brackets in wet condition using artificial saliva was adopted. The friction test was conducted by Instron Tinius Olsen testing device. The test was performed at a room temperature ranging from 24-25°C. Findings: Empower clear with Cu NiTi archwire showed the highest mean value of static frictional force with the mean value of (327.85±53.43) and Damon clear with epoxy coated NiTi archwire showed the lowest mean value (58.06±10.87). There were significant differences in the static frictional forces generated in both bracket systems when coupled with the Epoxy wires (p=0.000) and when coupled with the CuNiTi and Rhodium archwires (p=0.001). Conclusion: The result of this study showed that the Damon Clear brackets produce lower frictional forces than Empower Clear brackets and Epoxy-coated NiTi archwires can produce lower static frictional force compared to Rhodium-coated NiTi and CuNiTi archwires.